The Governance of Private Security - Boggero, Marco (Springer International Publishing, 2018)
This book offers new insights and original empirical research on private military and security companies (PMSCs), including China's negotiation approach to governance, an account of Nigeria's first engagement with regulatory cooperation under the threat of Boko Haram, and a study of PMSCs in Ebola-hit Western Africa. The author engages with concepts and theories from IR, Political Economy, and African studies-like regime, forum shopping, and extraversion-to describe what shapes state choices in national and international fora. The volume clarifies and spells out the needed questions and definitions and proposes a synthesis of how regime formation is shaped by ideas, interests, and institutions, starting from the proposition that regulatory cooperation consists in facilitating the acceptance and use of a single identifier for private military and security companies. Marco Boggero teaches global policy at the School of Advanced International Studies, Johns Hopkins University, USA.